Differential Physiological Responses Elicited by Ancient and Heritage Wheat Cultivars Compared to Modern Ones - Spisni, Enzo; Imbesi, Veronica; Giovanardi, Elisabetta; Petrocelli, Giovannamaria; Alvisi, Patrizia; Valerii, Maria Chiara (Nutrients, 2019)
Although ancient, heritage, and modern wheat varieties appear rather similar from a nutritional point of view, having a similar gluten content and a comparable toxicity linked to their undigested gluten peptide, whenever the role of ancient end heritage wheat grains has been investigated in animal studies or in clinical trials, more anti-inflammatory effects have been associated with the older wheat varieties. This review provides a critical overview of existing data on the differential physiological responses that could be elicited in the human body by ancient and heritage grains compared to modern ones. The methodology used was that of analyzing the results of relevant studies conducted from 2010 through PubMed search, by using as keywords “ancient or heritage wheat”, “immune wheat” (protein or peptides), and immune gluten (protein or peptides). Our conclusion is that, even if we do not know exactly which molecular mechanisms are involved, ancient and heritage wheat varieties have different anti-inflammatory and antioxidant proprieties with respect to modern cultivars. It is, therefore, reasonable to assume that the health proprieties attributed to older cultivars could be related to wheat components which have positive roles in the modulation of intestinal inflammation and/or permeability.